2009
DOI: 10.1038/emboj.2009.22
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional serine protease primes the malaria parasite for red blood cell invasion

Abstract: The malaria parasite Plasmodium falciparum replicates within an intraerythrocytic parasitophorous vacuole (PV). Rupture of the host cell allows release (egress) of daughter merozoites, which invade fresh erythrocytes. We previously showed that a subtilisin-like protease called PfSUB1 regulates egress by being discharged into the PV in the final stages of merozoite development to proteolytically modify the SERA family of papain-like proteins. Here, we report that PfSUB1 has a further role in 'priming' the meroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
202
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(217 citation statements)
references
References 54 publications
8
202
0
7
Order By: Relevance
“…However, although genetic approaches have shown that SUB3 is dispensable for the development of Plasmodium blood stages 11 , its precise biological role remains to be established 12 ; SUB1 and SUB2 are essential enzymes 11,13 . SUB1 executes the specific processing of proteins involved in the egress of Plasmodium merozoites (Mz) from host hepatocytes or erythrocytes 11,14 , as well as Mz protein surface maturation 15 . SUB2 carries out processing of proteins involved in Mz invasion into erythrocytes 8,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, although genetic approaches have shown that SUB3 is dispensable for the development of Plasmodium blood stages 11 , its precise biological role remains to be established 12 ; SUB1 and SUB2 are essential enzymes 11,13 . SUB1 executes the specific processing of proteins involved in the egress of Plasmodium merozoites (Mz) from host hepatocytes or erythrocytes 11,14 , as well as Mz protein surface maturation 15 . SUB2 carries out processing of proteins involved in Mz invasion into erythrocytes 8,16 .…”
mentioning
confidence: 99%
“…Subsequently, SUB1 matures the serine-rich repeat antigens (SERAs) 11 , a serine and papain-like family of proteases that participates in the rupture of the PV and infected RBC membranes 26 . In addition, SUB1 processes several parasite surface proteins, priming Mz for subsequent invasion of new erythrocytes 14,15,27 .…”
mentioning
confidence: 99%
“…At least two of these are mediated by subtilisin-like serine proteases: SUB1 and SUB2. SUB1 is released into the parasitophorous vacuole (PV) and is responsible for the so-called 'primary processing' of a number of accessible proteins, including merozoite surface proteins MSP1, MSP3, MSP6 and MSP7, as well as PV proteins of the SERA family (Koussis et al, 2009). SUB2 is a membrane-associated protease released on to the merozoite surface.…”
Section: -Biological Processes From a Signalling Perspectivementioning
confidence: 99%
“…In Plasmodium falciparum, SUB1 was shown to have a dual function. It is crucial for merozoite egress from erythrocytes and renders released merozoites competent for a new round of erythrocyte invasion (18,21). In the process of P. falciparum merozoite egress from erythrocytes, SUB1 carries out the maturation of the family of papain-like proteases called serine repeat antigens (SERAs) (18,19,22).…”
mentioning
confidence: 99%
“…It remains unknown whether the SERAs have a direct role in membrane disruption or whether they in turn maturate other effectors, but it is established that their SUB1-dependent maturation is essential for the egress of merozoite (18). The reported role of SUB1 in P. falciparum merozoite invasion is to undertake the processing of merozoite surface proteins (MSPs), including MSP1, the major merozoite surface protein and a leading malaria vaccine candidate (21). After SUB1 maturation, the membrane-anchored C-terminal 42-kDa fragment of MSP1 remains associated with the other MSP1 fragments and additional partners, including MSP6 and MSP7 (21,23), which are also processed by SUB1 (21).…”
mentioning
confidence: 99%